Evaluation of the physical and antifungal effects of chlorhexidine diacetate incorporated into polymethyl methacrylate - Caroline Vieira Maluf; Luciana Vieira Peroni; Lívia Rodrigues Menezes; Wagner Coutinho; Eduardo José Veras Lourenço; Daniel de Moraes Telles (University of São Paulo, 2020)
Abstract This study aimed to evaluate the physical properties and antifungal activities of polymethyl methacrylate (PMMA) acrylic resins after the incorporation of chlorhexidine diacetate salt (CDA). Methodology: First, acrylic resin specimens were fabricated with Vipi Cor® and DuraLay® resins with and without the incorporation of 0.5%, 1.0% or 2.0% CDA. The residual monomer and CDA release were measured at intervals ranging from 2 hours to 28 days using ultraviolet spectrometry combined with high-performance liquid chromatography. The antifungal activity against C. albicans was evaluated with the agar diffusion method. Fourier transform infrared spectroscopy was used to analyze the degree of resin conversion. Finally, the water sorption values of the resins were also measured. Results: The incorporated CDA concentration significantly changed the rate of CDA release (p<0.0001); however, the brand of the material appeared to have no significant influence on drug release. Subsequently, the inhibition zones were compared between the tested groups and within the same brand, and only the comparisons between the CDA 2% and CDA 1% groups and between the CDA 1% and CDA 0.5% groups failed to yield significant differences. Regarding the degrees of conversion, the differences were not significant and were lower only in the CDA 2% groups. Water sorption was significantly increased at the 1.0% and 2.0% concentrations. Conclusions: We concluded that the incorporation of CDA into PMMA-based resins enabled the inhibition of C. albicans growth rate, did not alter the degrees of conversion of the tested resins and did not change the release of residual monomers.